(Non)success of Transitional Reforms in the Countries of Former Yugoslavia - Božić Miljković, Ivana М. (Sociološki pregled, 2019)
The paper analyzes the economic effects of the transition process in the countries of the former Yugoslavia, with particular reference to those segments of that process that define the directives for their economic and institutional development. The results of the transition process are also analyzed in terms of the position of these countries vis-à-vis the European Union. The countries of the former Yugoslavia have achieved different results in the transition period so far in terms of membership in this integration and these results have been accepted by some researchers as the standard for evaluating their success in the transition process. If one assumes that membership in the Union alone is a “certificate of success” and an indicator of the end of the transition process, it can be said that only Slovenia and Croatia have succeeded in implementing the transitional reforms. However, according to economic indicators, the two countries share the fate of the other former Yugoslav republics and their success in the transition process is judged to be modest.
Keywords: transition; reforms; economy; former Yugoslavia; European Union